2021
DOI: 10.12688/f1000research.53962.1
|View full text |Cite
|
Sign up to set email alerts
|

Performing post-genome-wide association study analysis: overview, challenges and recommendations

Abstract: Genome-wide association studies (GWAS) provide  huge information on statistically significant single-nucleotide polymorphisms (SNPs) associated with various human complex traits and diseases. By performing GWAS studies, scientists have successfully identified the association of hundreds of thousands to  millions of SNPs to a single phenotype. Moreover, the association of some SNPs with rare diseases has been intensively tested. However, classic GWAS studies have not yet provided solid, knowledgeable insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 104 publications
(136 reference statements)
0
7
0
1
Order By: Relevance
“…The application of standard GWA analysis is not possible in this context, as this approach stratifies for the outcome of interest by selecting a subset of the population willing to participate. LD-independent SNPs reaching genome-wide Article https://doi.org/10.1038/s41562-023-01579-9 significance (P < 5 × 10 −8 ) were selected via clumping (clump-kb, 250; clump-r2, 0.1; following standard recommendations 43 ). PhenoScanner 44 , a database of genotype-phenotype associations from existing GWA studies, was used to explore previously identified associations of lead SNPs with other phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The application of standard GWA analysis is not possible in this context, as this approach stratifies for the outcome of interest by selecting a subset of the population willing to participate. LD-independent SNPs reaching genome-wide Article https://doi.org/10.1038/s41562-023-01579-9 significance (P < 5 × 10 −8 ) were selected via clumping (clump-kb, 250; clump-r2, 0.1; following standard recommendations 43 ). PhenoScanner 44 , a database of genotype-phenotype associations from existing GWA studies, was used to explore previously identified associations of lead SNPs with other phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Clumping based on Linkage Disequilibrium (LD) is a process used in genetic studies to identify and retain only the most significantly associated variants within a region of linkage disequilibrium (LD) [19, 20]. This is done to reduce redundancy due to the correlation between variants in close proximity to each other.…”
Section: Introductionmentioning
confidence: 99%
“…These methods take account of relatedness between individuals with mixed models and different algorithms to improve detection and/or approximations for a very large sample size. Post-association analysis, which may include highly complex methods such as meta analysis considering different GWAS summary statistics, fine-mapping to define causal variants, heritability of phenotype, replication and transferabilty of previous results, annotation, integration of eQTL, and/or calculation of polygenic risk score [ 5 ]. …”
Section: Introductionmentioning
confidence: 99%
“…Post-association analysis, which may include highly complex methods such as meta analysis considering different GWAS summary statistics, fine-mapping to define causal variants, heritability of phenotype, replication and transferabilty of previous results, annotation, integration of eQTL, and/or calculation of polygenic risk score [ 5 ].…”
Section: Introductionmentioning
confidence: 99%